2018
DOI: 10.1001/jamanetworkopen.2018.0210
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Follow-up Care After Emergency Department Presentation for Mild Traumatic Brain Injury and Concussion

Abstract: Key Points Question Do patients with mild traumatic brain injury (mTBI) receive adequate levels of follow-up care? Findings In a cohort study using data on 831 patients with mTBI presenting to the emergency department at 1 of 11 level I trauma centers across the United States, 42% of patients reported receiving educational material at discharge and 44% reported seeing a physician or other medical practitioner within 3 months after injury. Among patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
104
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 140 publications
(122 citation statements)
references
References 32 publications
4
104
1
2
Order By: Relevance
“…Of nearly 2.8 million TBI cases in the US [2], mild TBI accounts for over 75-80% cases [3,4]. mTBI is conventionally diagnosed based on the following three criteria: (a) loss of consciousness shorter than 30 min; (b) post-traumatic amnesia shorter than 24 hours; and (c) when the injury is scored 13 to 15 on the Glasgow Coma Scale (GCS) (moderate TBI by 9-12 and severe TBI by [3][4][5][6][7][8] [1,5]. Although the injury is classified as 'mild', mTBI can cause multifaceted and persistent functional impairments.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Of nearly 2.8 million TBI cases in the US [2], mild TBI accounts for over 75-80% cases [3,4]. mTBI is conventionally diagnosed based on the following three criteria: (a) loss of consciousness shorter than 30 min; (b) post-traumatic amnesia shorter than 24 hours; and (c) when the injury is scored 13 to 15 on the Glasgow Coma Scale (GCS) (moderate TBI by 9-12 and severe TBI by [3][4][5][6][7][8] [1,5]. Although the injury is classified as 'mild', mTBI can cause multifaceted and persistent functional impairments.…”
Section: Introductionmentioning
confidence: 99%
“…Although the injury is classified as 'mild', mTBI can cause multifaceted and persistent functional impairments. Such persistent and chronic, often untreated, impairments can severely disturb the quality of life of affected individuals [6]. While most post-mTBI functional deficits may recover in 3 to 6 months [7], up to 40% of affected individuals [8][9][10] suffer from 3 All subjects submitted their informed consent for inclusion before they participated in the study.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of a national survey of 35 Level I trauma centers in the United States showed that only 34% of centers referred patients with mTBI for further evaluation . An additional study showed that as many as 40% of patients do not receive follow‐up care within 3 months of their TBI . Studies have shown that 52% of patients with mTBI reported persistent, injury‐related deficits 12 months after the date of injury.…”
Section: Introductionmentioning
confidence: 99%
“…4 An additional study showed that as many as 40% of patients do not receive follow-up care within 3 months of their TBI. 5 Studies have shown that 52% of patients with mTBI reported persistent, injury-related deficits 12 months after the date of injury. Additionally, it is suggested that mTBI is associated with as much as a 75% increase in medical costs up to 3 years after injury 6 and that the lasting effects of TBI may also contribute to loss of employment, homelessness, and incarceration.…”
Section: Introductionmentioning
confidence: 99%